uₜ (x,t) = k(uₓₓ(x,t) - 2auₓ(x,t) + bu(x,t)), 0 < x < l, t > 0
u(0,t) = 0, u(l,t) = 0 and u(x,0) = f(x)
Hint: Use substitution
u(x,t) = eᵃˣ⁺βᵗ v(x,t), β = k(b - a²)
These solutions may offer step-by-step problem-solving explanations or good writing examples that include modern styles of formatting and construction of bibliographies out of text citations and references. Students may use these solutions for personal skill-building and practice. Unethical use is strictly forbidden.
By purchasing this solution you'll be able to access the following files: